PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS SAINTIFIK PADA MATERI IPA DI KELAS V SD INPRES MINASA UPA 1 KECAMATAN RAPPOCINI KOTA MAKASSAR - Andi Makkasau; Muhammad Irfan; Syamsuddin; Nur Azizah (STKIP Subang, 2022)
This research is a type of Research and Development (RnD) research that aims to find out how to develop scientific-based worksheets on science material for fifth grade students. This study uses the ADDIE development model, which consists of 5 stages, namely the analysis stage, the design stage. (Design), the development stage (Development), the implementation stage (Implementation), and the evaluation stage (Evaluation). The research instrument used is a questionnaire in the form of a validation questionnaire to determine the validity of the developed product and the user's response to the questionnaire to determine the product developed by using a Likert scale calculation. The resulting product is a scientific-based worksheet which was developed using the Power Point 2010 application. The product developed was validated by one material expert and one media expert and implemented in a trial given to 12 students and one class VB teacher at SD Inpres Minasa Upa 1. Validation is carried out to determine the validity of the developed-based LKPD. The results of the validation by the material expert validator were obtained at 96.7% in the very valid category and the validation by the media expert validator obtained at 99.1% with the very valid category. The user responses given by students and teachers are carried out to be adjusted according to scientific-based LKP. The results given by students and teachers were respectively 87.7% and 97.2% with a very decent category. So that the scientific-based LKPD is valid and feasible to be applied in learning.